PENERAPAN PENCANTUMAN IDENTITAS NARASUMBER PADA PEMBERITAAN DI RADAR BOGOR DALAM KODE ETIK JURNALISTIK - Hidayat, Fathya Kayla; Ratnamulyani, Ike Atikah; Fitriah, Maria (Universitas Djuanda Bogor, 2019)
The inclusion of a source identity is something that must be applied to a news. A journalist can maintain the confidentiality of sources of confidential information, the identity of victims of sexual crimes, and perpetrators or victims of underage crimes. This study uses a qualitative approach and descriptive analysis research method by performing data retrieval techniques using primary data and secondary data. Primary data are the results of field observations, interviews. While secondary data is in the form of documentation. The object of research is the Radar Bogor Journalist. The results showed that journalists from Radar Bogor had implemented a journalistic code of ethics in the inclusion of the identity of the informant on a report. This is seen from the attitude of conscious journalists to maintain the confidentiality of the identity of informants such as victims of immoral crimes, victims of sexual abuse, underage victims, and victims of sexual abuse. This is feared by the psychological sources who receive social sanctions from the community. Keywords: The News; Inclusion of identity; Journalistic Code of Ethics.